Literature in Our Time, or, Loving Literature to Bits. Issue 2 (August 2015) - Callus, Ivan
<x content-type="archive" xml:space="preserve">Abstract</x> In this essay Ivan Callus provides some reflections on literature in the present. He considers the tenability of the post-literary label and looks at works that might be posited as having some degree of countertextual affinity. The essay, while not setting itself up as a creative piece, deliberately structures itself unconventionally. It frames its argument within twenty-one sections that are self-contained but that also echo each other in their attempt to develop an overarching argument which draws out some of the challenges that lie before the countertextual and the post-literary. Punctuating the essay and contributing to its unconventional take on the practice of literary criticism is a series of exercises for the reader to complete, if so wished; the essay makes no attempt, however, to suggest that a countertextual criticism ought to make a routine of such devices. The separate sections contain reflections on a number of texts and writers, among them, and in order of appearance, Hamlet, Anthony Trollope, Jacques Derrida, The Time Machine, Don Quixote, Mark Z. Danielewski, Mark B. N. Hansen, Gunter Kress, Scott's Reliquiae Trotcosienses, W. B. Yeats, Kate Tempest, David Jones, Anne Michaels, Bernice Eisenstein, Paul Auster, J. M. Coetzee, Billy Collins, Deidre Shauna Lynch, Tim Parks, Tom McCarthy – and Hamlet again. The essay's length fulfils a performative function but also facilitates as extensive a catalogue of aspects of the countertextual in literature and elsewhere as is feasible or as might be dared at this stage.